Analisis Upaya Peningkatan Literasi di Kelas 2 SD Pada Era New Normal - 'Adawiyyah, Robi'atul; Ermawati, Diana; Fardani, Much. Arsyad (Journal Prakarsa Paedagogia, 2023)
The purpose of this study is to analyze efforts to increase literacy in SD 3 Rejosari in the new normal era.This study used a qualitative method with a case study approach. The subjects of this study were teacher of grade 2 SD 3 Rejosari and students of grade 2 SD 3 Rejosari. Data from this study were obtained using interview, observation, and documentation techniques. Validity test of the data using the credibility, transferability,dependability, konfirmability. Data analysis used an intecrative model with the stages of data collection, data reduction, data display, and conclusion drawing.The results of the research conducted at SD 3 Rejosari included: 1) classifying students literacy abilities; 2) providing assistance according to the ability of students; 3) maximizing children’s books for reading materials; 4) create literacy friendly class; 5) make a daily reading journal